2019
DOI: 10.17163/soph.n27.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

O conceito de pensamento crítico de acordo com os professores de preservação chilenos

Abstract: El presente trabajo analiza el concepto de pensamiento crítico según la perspectiva de un grupo de estudiantes de pedagogía provenientes de una universidad chilena, quienes se encuentran cursando el cuarto año de su carrera. Veinte futuros profesores de diferentes programas de formación docente participaron de la muestra, con un método de recolección de datos centrado en la técnica del grupo focalizado, en el cual los participantes expresaron sus perspectivas respecto al tema. Las respuestas recogidas fueron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
2
3
0
8
Order By: Relevance
“…In addition, there are words still to be framed in the theoretical framework referred to by our students as Capacity-which is also the most frequent word among our students, Order, Assertive, Debug, Doubt, Guide, Judge, and Justify. In this sense, the results show a certain competence of the students of the Degree in Social Education in relation to the knowledge of what critical thinking is and means-of which they themselves are aware by their claims-and a coherent relationship between what they say and what the theoretical development of the same refers; in turn, they also understand theoretically the importance of acquiring critical competence, as well as the need for training; these results coincide with those obtained by Diaz et al [31] in his research with students of pedagogy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, there are words still to be framed in the theoretical framework referred to by our students as Capacity-which is also the most frequent word among our students, Order, Assertive, Debug, Doubt, Guide, Judge, and Justify. In this sense, the results show a certain competence of the students of the Degree in Social Education in relation to the knowledge of what critical thinking is and means-of which they themselves are aware by their claims-and a coherent relationship between what they say and what the theoretical development of the same refers; in turn, they also understand theoretically the importance of acquiring critical competence, as well as the need for training; these results coincide with those obtained by Diaz et al [31] in his research with students of pedagogy.…”
Section: Discussionsupporting
confidence: 87%
“…As far as we know, research on critical thinking in Social Education university students is almost non-existent. Within the educational field, we are only aware of the study of Díaz et al [31] which addresses the theoretical knowledge of students about critical thinking in a group of 4th year pedagogy students. There authors found that the most recurrent concepts regarding critical thinking were to analyze, reflect, reason, generate changes, and solve problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De esta manera, se puede considerar que los estudiantes tengan estas habilidades desarrolladas en sus procesos cognitivos, por formar parte de un sistema educativo que busca consolidar la formación de ciudadanos con estos principios (Díaz-Larenas, et al, 2019). Por otro lado, el pensamiento crítico se opone a la pasividad receptora de una mente que se deja moldear y modelar por las influencias del entorno; implica la autonomía del sujeto, superando la heteronomía propia de la escolaridad tradicional (Estrada-Zapata, 2019).…”
Section: Pensamiento Criticounclassified
“…25(1) ENERO-ABRIL, 2021: 1-11 dicho enfoque comprende, son: creatividad e innovación, pensamiento crítico, autoaprendizaje, comunicación, colaboración y trabajo en equipo, adaptabilidad, proactividad, orientación a resultados, liderazgo, responsabilidad y respeto (Bezanilla Albisua et al, 2018). Es decir, el pensamiento crítico es una macro habilidad compleja, pero necesarias en el estudiantado para un desarrollo de capacidades y dominios fundamentales en la educación (Díaz-Larenas et al, 2019).…”
Section: Introductionunclassified